A Review on Energy Storage Systems in Distributed Generation for Generation Expansion Planning Study - Arun Kumar A, B.V. Manikandan ,S. Kannan (International Journal of Advanced Science and Technology, 2020)
handled by the ESS which will improve energy utilization and reliability and hence the total cost of the GEP is minimized.Power System planning is an economic problem wherein the primary objective is to determine the minimum cost strategy for long term expansion of Generation, transmission and distribution systems while satisfying technical and environmental constraints. Generation Expansion Planning (GEP) is one of the important planning activities for the electric utilities. GEP is the problem of identifying the most adequate technology, expansion size, siting, and timing for the construction of new plants considering economic criteria while ensuring that the installed capacity adequately meet the expected demand growth. GEP has many objectives such as minimization of costs, minimization of pollutants/emissions and maximization of profit and maximization of system reliability. Distributed Generation (DG) helps the power system to minimize the cost, complexity and improve the efficiency in transmission and distribution. Renewable DG systems are becoming popular and it can be operated in grid-connected mode. Energy Storage System (ESS) is a key tool to smooth out the intermittent nature of the renewable DG especially for Wind and Solar energy.  ESS plays a vital role in micro grid as well as smart grid. In this paper, a review of ESS is done on the basis of several types. The integration of ESS will minimize the investment cost and emission of Green House Gases (GHG) to atmosphere in the system. The intermittent nature of the renewable sources is effectively